Authors' lack of awareness and use of core outcome set on postoperative pain in children is hindering comparative effectiveness research. (18th May 2018) - Boric, Krste; Boric, Matija; Dosenovic, Svjetlana; Jelicic Kadic, Antonia; Batinic, Marijan; Cavar, Marija; Jeric, Milka; Puljak, Livia
Aim: To analyze awareness about and acceptability of core outcome set (COS) for pediatric pain recommended by the PedIMMPACT.Methods: We invited authors of systematic reviews and randomized controlled trials about interventions for postoperative pain in children to participate in a survey.Results: Only a third of surveyed authors of systematic reviews and randomized controlled trials about postoperative pain in children had heard about the PedIMMPACT COS for acute pediatric pain. Problems indicated as preventing them from using the COS were lack of awareness, difficulties with implementation, and lack of resources.Conclusion: Further discussions about the adequacy of COS for acute pediatric pain, as well as interventions to increase the uptake of COS may be warranted.